Approaches for conceptualizing customer satisfaction and perceived service quality - MUNTHIU, Maria-Cristiana; RĂDULESCU, Violeta (Annals of Spiru Haret University. Economic Series, 2012)
Customer satisfaction and perceived service quality seem to be in a permanent struggle to get unspoiled attention from marketers; thus, service companies should be aware of various approaches for conceptualizing their similarities and differences. The relationship between these concepts seems to be unclear and, therefore, marketing specialists should constantly monitor the factors that influence customer satisfaction of services and the importance perceived service quality has among these factors.